Trust, Accountability and Capacity in Education System Reform Global Perspectives in Comparative Education - Ehren, Melanie; Baxter, Jacqueline (Taylor & Francis, 2021)
While Finland and Singapore both enjoy the global educational limelight due to their successful school systems, they differ considerably in their approaches to teacher accountability. Finland's light-touch teacher accountability system focuses on setting standards at the point of entry to the teaching profession, whereas Singapore uses a comprehensive, tiered, and competitive performance management system that deploys promotions and performance bonuses to manage the processes and outputs of teacher practice in schools. In this chapter, I use interviews with 24 Finnish and Singaporean teachers to explore the differences between these distinct approaches to teacher accountability-and to account for their disparate but apparently successful pathways. I argue that these disparate approaches share an underlying principle: each model of teacher accountability is compatible with the macrosystem in which it is embedded. Thus, teachers regard the accountability instruments as legitimate, enabling the instruments to favourably influence teacher motivation and practice. Specifically, public trust in Finland's education system is distributed throughout each level of the system, with teachers enjoying high generalised trust. This is compatible with an accountability approach that gives teachers considerable autonomy over their daily work. In contrast, public trust in Singapore's education system is concentrated on the Ministry of Education. This institutionally focused trust supports-and is supported by-a teacher accountability system that gives the managers considerable influence over teacher practice.